Using equidistant Vector-Based Hysteresis Current Regulator for DFIG Wind Turbines - Mohseni, Mansour; Islam, Syed; Masoum, Mohammad Sherkat (Elsevier S.A., 2011)
This paper proposes a novel equidistant vector-based hysteresis current regulator (VBHCR) in the rotor-side converter (RSC) of DFIG-based wind generation systems. The Γ-form equivalent circuit is used for the machine modelling, with the discrete formulation of the RSC output voltage. The overall vector control scheme is then explored and the control structure of the proposed equidistant VBHCR is presented. When compared to the commonly used PI current regulators, the proposed VBHCR exhibits several advantages such as very fast transient response, simple hardware implementation, satisfactory steady-state performance, and intrinsic robustness to machine parameters variations. Moreover, fixed hysteresis bands are replaced with equidistant bands in order to limit the instantaneous variations of the switching frequency and reduce the maximum switching frequency of the RSC. Detailed simulation studies are carried out for a 1.5 MW DFIG-based wind generator to examine the operation of the proposed current regulator under various operating conditions and demonstrate its superiority over the standard PI current regulator.